INSIGHT ANALYSIS ON DYKE PROTECTION AGAINST LAND SUBSIDENCE AND THE SEA LEVEL RISE AROUND NORTHERN COAST OF JAVA (PANTURA) INDONESIA - Heri Andreas; Hasanuddin Zainal Abidin; Dina Anggreni Sarsito; Dhota Pradipta (Department of Urban and Regional Planning, Diponegoro University, 2018)
Land subsidence and the sea level rise is newly well-known phenomenon around northern coast of Java Indonesia (PANTURA). The occurrence of land subsidence at least recognizes at the first of the city or urban area development, while the sea level rise was recognized from several last decades corresponds to the global warming. Following the both phenomena, tidal inundation (in Javanese they call it “Rob”) is now becoming another newly well-known phenomenon along PANTURA. In the recent years the tidal inundation comes not only at a high tide but even at the regular tide in some area. Sea level rise and the land subsidence are considered as the causes deriving the occurrence of tidal inundation. Dykes have been built against tidal inundation around PANTURA (e.g. in Jakarta, Blanakan, Pekalongan, Semarang, and Demak). Nevertheless, since the land subsidence and the sea level rise are believed to be continuing through times, insight analysis on these dyke’s “protector” is necessary. How long the dyke would effectively protect the land area would be highlight in this paper.